PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, TEKANAN ANGGARAN WAKTU DAN INDEPENDENSI AUDITOR TERHADAP AUDIT JUDGMENT (Studi Empiris pada Auditor Di Kantor Akuntan Publik Kota Pekanbaru dan Padang) - Prameswari, Shakila; Kamaliah, Kamaliah; Zarefar, Atika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to determine the effect of obedience pressure, task complexity, time budgetpressure, and independence on audit judgment. Audit judgment is a professional considerationof auditors in the audit process, which greatly affects the quality of the opinion given. Thisstudy was conducted empirically on auditors working in Public Accounting Firms (KAP) in thecities of Pekanbaru and Padang. The method used is a quantitative method with data collectiontechniques through questionnaires distributed to auditors in 14 KAPs. The collected data wereanalyzed using multiple linear regression analysis. The results of the study indicate thatobedience pressure, task complexity, and time budget pressure have a significant effect on auditjudgment, while independence does not have a significant effect. This study is expected to bean input for auditors to improve the quality of audit judgment by considering the factors thatcan influence it.Keywords: Audit Judgment, Obedience Pressure, Task Complexity, Time Budget Pressure,Independence